The Mannose-Sensitive Hemagglutinin of Vibrio cholerae Promotes Adherence to Zooplankton - Chiavelli, Deborah A. (American Society for Microbiology, 2001)
The bacterium Vibrio cholerae, the etiological agent of cholera, is often found attached to plankton, a property that is thought to contribute to its environmental persistence in aquatic habitats. The V. cholerae O1 El Tor biotype and V. cholerae O139 strains produce a surface pilus termed the mannose-sensitive hemagglutinin (MSHA), whereas V. cholerae O1 classical biotype strains do not. Although V. cholerae O1 classical does not elaborate MSHA, the gene is present and expressed at a level comparable to that of the other strains. Since V. cholerae O1 El Tor and V. cholerae O139 have displaced V. cholerae O1 classical as the major epidemic strains over the last fifteen years, we investigated the potential role of MSHA in mediating adherence to plankton. We found that mutation of mshA in V. cholerae O1 El Tor significantly diminished, but did not eliminate, adherence to exoskeletons of the planktonic crustacean Daphnia pulex. The effect of the mutation was more pronounced for V. cholerae O139, essentially eliminating adherence. Adherence of the V. cholerae O1 classical mshA mutant was unaffected. The results suggest that MSHA is a factor contributing to the ability of V. cholerae to adhere to plankton. The results also showed that both biotypes of V. cholerae O1 utilize factors in addition to MSHA for zooplankton adherence. The expression of MSHA and these additional, yet to be defined, adherence factors differ in a serogroup- and biotype-specific manner.